Information visualization in open data dissemination environments: a study on information observatories of the industry federations of Brazil (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
This article presents an ongoing study on the information observatories of the Industry Federations in Brazil, which are responsible for providing relevant and effective information for decision-making in the industrial sector. The objective of the study is to analyze the informational and organizational maturity of these observatories and understand how they employ concepts, techniques, and technologies to fulfill their intent. The article adopts an exploratory and constructivist approach, with qualitative analysis complemented by quantitative methods as needed. It is based on bibliographic and documentary analysis, utilizing materials available on virtual platforms during the observation process. The analyzed observatories are in eight Brazilian states and have well-established information processes based on an adapted conceptual model of information observatories proposed by Gomes et al. (2016). The results of this study include an important literature review on information observatories and the discipline of Information Visualization, as well as the identification of best practices used by the Industry Federation observatories.